The Effects of Environmental Orientation on Firm Performance and a Mediating Role of Employee-Based Brand Equity: A Comparative study - Wisker, Zazli Lily; Kwiatek, Piotr (AIBPM Publisher, 2018)
The studies striving to investigate the interrelationships between environmental orientation-company’s performance, and its mediator constructs remain fragmented. This study provides insights to illuminate the process through which environmental orientation transfers into business results. It proposes hypotheses based on Social Identity Theory and the Theory of Reasoned Action and empirically test it in a comparative, cross-cultural study. The findings observe that employee-specific idiosyncrasies influence business performance through employee-based brand equity. Thus, the study suggests an increased role for management-induced practices to effectively transform brand values into a higher level of employee engagement and better business results.